2017
DOI: 10.1039/c6bm00629a
|View full text |Cite
|
Sign up to set email alerts
|

A database on the stability of silver and gold nanostructures for applications in biology and biomolecular sciences

Abstract: Colloidal stability of nanoparticles in biological media is an important consideration when trying to ensure reliable data interpretation of in vitro and in vivo systems. We have developed a detailed colloidal stability library of newly synthesized gold, silver and gold-core silver-shell plasmonic nanoparticles, stabilized with aspartame, glucosamine and sucralose, in various biologically relevant buffers and bacterial and mammalian cell culture media. The stabilizer selection reflects the preference for molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…peptidoglycan layer present in the bacterial cell wall can help to attract sugars, and with them the nanocomposites attached. 17,47 As mentioned before, there are two main processes that are believed to be involved in the photo-induced antimicrobial activity of MNP, 12,13 namely, photothermal and photochemical mechanisms. The rst one involves the absorption of light by the MNP and the concomitant local release of heat from the particle that can destroy biomolecules (or melt the lipids in a cell membrane) in close proximity to the MNP surface.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…peptidoglycan layer present in the bacterial cell wall can help to attract sugars, and with them the nanocomposites attached. 17,47 As mentioned before, there are two main processes that are believed to be involved in the photo-induced antimicrobial activity of MNP, 12,13 namely, photothermal and photochemical mechanisms. The rst one involves the absorption of light by the MNP and the concomitant local release of heat from the particle that can destroy biomolecules (or melt the lipids in a cell membrane) in close proximity to the MNP surface.…”
Section: Discussionmentioning
confidence: 97%
“…Coincidentally, these nanocomposites contain lignin with higher sugar content, which could contribute to a better interaction with the S. aureus bacterial cell wall. 17,47 Additionally, Fig. S9 † shows the AuNP@lignin tested are non-toxic for the bacteria in the dark, unless they are subjected to light exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essam et al reported that AgNPs produced by Bacillus licheniformis showed that the zeta potential ranged from À16.6 to À21.3 mV was quite stable, demonstrated excellent in vitro antimicrobial activity against important human pathogens and antiviral activity against the Bean Yellow Mosaic Virus [41]. Thus, the negative surface charge is highly responsible for providing the colloidal stability to nanoparticles, especially in biological environments [42].…”
Section: Nanoparticles Characterizationmentioning
confidence: 99%
“…Stability was considered as the time it took for a 20% decrease in plasmon absorption at the wavelength of the initial maximum absorbance. 8 The stability measurements were carried out (using a BioTek plate reader) for 7 days (time = 0, 0.5, 1, 2, 4, 6, 12 18, 24, 48, 72, 120, 144, 168 h) in Milli-Q water, saline solution, PBS (pH = 7), Mueller Hinton broth (MHB), and tryptic soy broth (TSB) at different concentrations (100, 50, 25, 12.5%). To avoid contamination, the stability measurement of nanoparticles dispersed in growth media was conducted under sterile conditions.…”
Section: Methodsmentioning
confidence: 99%